Prediction of morbidity and mortality in middle and old aged surgical patients-comparison of standard scoring system and addition of echocardiography with hemodynamic indices - Singh, Amit K.; Mishra, Prashant K.; Singh, Rakesh B.; kumar, Manoj; Singh, Dheer (International Journal of Research in Medical Sciences, 2017)
Background: A prospective study was carried out in our hospital to predict morbidity and mortality in middle and old aged surgical patients by adding echocardiography to standard scoring system with hemodynamic studies. Methods: A total of 50 patients of either sex ranging from 40-70 years of ASA grade 1 & 2 scheduled for various types of noncardiac surgeries were enrolled for the study in our hospital. Patients were divided in two groups according to echocardiographic examinations. The patients with normal echocardiographic values were kept in control group and the patients with abnormal values were kept under study group. The patients in study group were further divided in three groups according to LVEF. Group1-LEVF≥60%, Group2-LVEF≥50-59%, Gr3≥40-49% Tab lorazepam was given to all the patients’ orally prior night of surgery. All the patients were induced with same type inducing agents according to body weight. All the patients were maintained on IPPV by anaesthesia machine with supplemental fentanyl, N2O, O2 and muscle relaxant. SPO2, electrocardiograph (ECG), Non-invasive/invasive blood pressure (BP), Spirometry, Capnography and temperature were monitored. At the end of the research project data’s were compiled systematically and were subjected to statistical analysis using odd’s ratio(OR),95% confidence interval (CI), z value and p value, two statistical software programme were used. Results: Significant difference in the results seen between the three study groups (Gr1, Gr2, Gr3) for perioperative ischemic changes, CHF and arrhythmias. Conclusions: In conclusion preoperative TTE before non-cardiac surgery can predict the risk of perioperative cardiac complications in known or suspected cases of cardiac disease patients.